Islamicity of Banking and Modes of Islamic Banking - Muhammad Anwar, (2000)
Economists, bankers, jurists, and other Islamic scholars interested in the discipline of banking have mainly focused on the issue of whether interest is riba, and if yes then how to conduct interest-free banking? To this end, several alternatives to interest have discovered and very successfully put into practice by the contemporary Islamic banks. The alternatives include some trading models like murabaha, bai mu'ajjal, bai salam, bai eenah and others. The currents study identifies a major problem in using these trading modes for the purpose of financing. This analysis also uncovers some other discrepancies between application of these modes and related injunctions from the Qur'an and Sunnah. The concentration on the issue of riba in banking system itself, comprising central banks and commercial banks, irrespective of the use of interest, is consistent with the injunctions of Islam. The concepts of the Money Expansion Multiplier and Quantity Theory of Money reveal that the central banks and commercial banks, irrespective of the use of interest, is consistent with the injunctions of Islam. The concepts of the Money Expansion Multiplier and Quantity Theory of money reveal that the central banks and commercial banks usurp people's property in the form of seignorage by expanding money supply. Such outcome is also condemned by express verses in the Qur'an. It is therefore concluded that the entire banking system and the operations of contemporary Islamic banks are of doubtful validity. Hence some measures are suggested for restructuring of banking to advance the cause of Islamization.